Kemampuan Belajar Siswa Kelas Viii Pada Mata PelajaranIlmu Pengetahuan Sosial Ditinjau Dari Minat BelajarSiswa Dan Persepsi Siswa Tentang KeterampilanMengajar Guru Di Smp Islam KedungKabupaten Jepara TahunPelajaran 2016/2017 - Setyawan, Edy; Suwandi, M.Pd, Drs. Djoko Suwandi, M.Pd (2016)
The purpose of this study was to determine: 1) To analyze the effect of student interest to the students' learning ability. 2) To determine the effect of students perceptions about the teaching skills of teachers to students' learning ability. 3) To determine the effect of student interest and student perceptions about the teaching skills of teachers to students' learning ability. This research is quantitative research with descriptive approach. The population in this study are all students of class VIII SMP Islam Kedung Jepara regency Force Year 2016/2017. samples are taken as 119 students by random sampling. Necessary data obtained through questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, t-test, F, and the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 3.051 + 0.368 X1 + 0.068 X2. The equation shows that the students 'learning ability is influenced by student interest and student perceptions of teachers' teaching skills. The conclusions drawn are: 1) Interest in learning students' learning ability of students can be accepted. This is based on multiple linear regression analysis (t test) note that tcount> ttable, 8.269> 2.000 and the significance value <0.05, namely 0.000 with the relative contribution of 67% and the effective contribution 18,943,1%. 2) Students 'perceptions about the teaching skills of teachers to students' learning ability can be accepted. This is based on multiple linear regression analysis (t test) note that tcount> ttable, namely 4.259> 2.000 and the significance value <0.05, namely 0.000 with the relative contribution of 33% and the effective contribution of 21.2%. 3) The interest of student learning and student perceptions about the teaching skills of teachers to student learning ability in conducting academic registration can be accepted. This is based on multiple linear regression analysis of variance (F test) is known that F count> F table, ie 310.831> 3.150 and the significance value <0.05, namely 0.000. 4) The coefficient of determination (R2) of 0.643 indicates that the influence of student interest and student perceptions about the teaching skills of teachers to students' learning ability is 64.3%, while the rest influenced by other variables.